Finnish children producing English vowels - Studying in an English immersion class affects vowel production - Katja Immonen; Maija S. Peltola (Academy Publication, 2022)
The aim of this study was to examine how earlier second language teaching affects Finnish school children’s pronunciation of British English vowels. Two groups of Finnish children between the ages of eleven and thirteen were tested. The early learners studied in an English immersion class in a Finnish elementary school while the control group attended a regular Finnish speaking class at the same school. The task consisted of twenty three English stimulus words which included the twelve monophthong English target vowels in voiced and voiceless environments. The words were repeated seven times during the task. The participants produced the words after a native model and the target vowel qualities were then acoustically analysed. Statistical analysis revealed a group main effect. More specifically the analysis showed that the groups differed significantly in the way they produced target vowel second formant (F2) values. The F2 difference was only significant in the voiced context. Closer examination of the groups’ vowel qualities revealed that the control group tended to produce the F2 values higher than the early learner group in most of the target vowels. The higher F2 values can be an indication of more frontal tongue position or less lip rounding during vowel production.